2004
DOI: 10.1207/s15327914nc5002_5
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study: Effect of 3,3′-Diindolylmethane Supplements on Urinary Hormone Metabolites in Postmenopausal Women With a History of Early-Stage Breast Cancer

Abstract: Dietary indoles, present in , and cortisol in the first morning urine sample before intervention and 31 days after intervention. Nineteen women completed the study, for a total of 10 in the treatment group and 9 in the placebo group. DIM-treated subjects, relative to placebo, showed a significant increase in levels of 2-OHE 1 (P = 0.020), DIM (P = 0.045), and cortisol (P = 0.039), and a nonsignificant increase of 47% in the 2-OHE 1 /16 α-OHE 1 ratio from 1.46 to 2.14 (P = 0.059). In this pilot study, DIM incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 47 publications
6
55
0
Order By: Relevance
“…In controlled clinical trials, oral supplementation with 300-400 mg/d of I3C has consistently increased urinary 2OHE 1 levels or urinary 2OHE 1 :16αOHE 1 ratios in women [93][94][95][96][97]. Supplementation with 108 mg/day of DIM also increased urinary 2OHE 1 levels in postmenopausal women [98]. However, the relationship between urinary 2OHE 1 :16OHE 1 ratios and breast cancer risk is not clear.…”
Section: Effects Of Indole-3-carbinol On Estrogen Metabolismmentioning
confidence: 99%
“…In controlled clinical trials, oral supplementation with 300-400 mg/d of I3C has consistently increased urinary 2OHE 1 levels or urinary 2OHE 1 :16αOHE 1 ratios in women [93][94][95][96][97]. Supplementation with 108 mg/day of DIM also increased urinary 2OHE 1 levels in postmenopausal women [98]. However, the relationship between urinary 2OHE 1 :16OHE 1 ratios and breast cancer risk is not clear.…”
Section: Effects Of Indole-3-carbinol On Estrogen Metabolismmentioning
confidence: 99%
“…When compared with placebo, BR-DIM resulted in a significant increase in 2OHE 1 (P ¼ 0.02) and a modestly protective shift in the 2OHE 1 :16aOHE 1 ratio (P ¼ 0.059). 84 The ability of DIM to induce CYP enzymes responsible for catalyzing hydroxylation could be responsible for the enhanced production of 2OHE 1 and the limited production of 16aOHE 1 . Additionally, administration of BR-DIM to premenopausal women improves symptoms of cyclical mastalgia, 85 a potential indicator of increased breast cancer risk.…”
Section: Mechanisms Of Action and Surrogate Endpoints In Humansmentioning
confidence: 99%
“…These dose levels produced significant changes in the activities of at least two xenobiotic and steroid-metabolizing enzymes and markedly altered the ratio of hydroxylated estrone metabolites in a manner consistent with chemoprevention. The use of 400 mg of I3C daily seems to be safe and effective supplement for women [106,107,109,110]. Other study indicated that DIM supplementation at a dose of 108 mg/day for 30 days increased urinary 2-hydroxyestrone excretions in postmenopausal women with a history of breast cancer [110].…”
Section: Human Clinical Studiesmentioning
confidence: 94%